The psychological illness of police officers in the exercise of their profession - Pinheiro , Ana Patrícia de Oliveira Ribeiro Silva; Musser , Paula Maria Grave; Melo, Adriana Soely André de Souza (Seven Editora, 2024)
The emotional coercion exercised on police officers in society can lead to several consequences that are in the public interest. Dealing with the continuous coercion directed at the police officer, in view of the role assigned to him to prevent and combat violence in the social sphere, generates some complications from physical to psychological exhaustion. Seeking to understand the phenomena that occur, namely anxiety disorders, depression and often suicide, has been an arduous task and has shown some success since the 90s through studies observing groups of police officers. In the research, a subcategory of psychiatry is created, sicidiology, which was created to analyze these phenomena more deeply and thus elucidate other disorders that contribute to their worsening in relation to the group in question. DOI:https://doi.org/10.56238/sevened2024.018-019